'Simple' can be good, too: testing three hard bottom sampling methods on macrobenthic and meiobenthic assemblages. (24th October 2018) - Keklikoglou, Kleoniki; Chatzigeorgiou, Georgios; Faulwetter, Sarah; Kalogeropoulou, Vassiliki; Plaiti, Wanda; Maidanou, Maria; Dounas, Costas; Lampadariou, Nikolaos; Arvanitidis, Christos
Abstract: Subtidal hard bottoms are of particular scientific and economic value as they are highly productive systems. They are less well studied compared with soft bottoms, as they often require manual sample collection via scuba diving. Although a multitude of sampling devices is available for soft bottoms, only a few are suitable for hard substrates, and their performance is largely unstudied. In the present study, three hard bottom sampling methods were compared, regarding their sampling efficiency and the damage they may cause to macrobenthic and meiobenthic organisms. Two of the sampling methods examined are typically employed for the study of hard bottom substrates (manual collection, airlift device), while the third involves a newly constructed sampler (MANOSS – Manual Operated Suction Sampler). All three sampling methods were tested at 12 m depth on a hard bottom substrate with algal coverage dominated by Cystoseira spp. No overall significant differences were observed between the sampling efficiency and the damage caused by the three sampling methods regarding the macrofaunal assemblages, with the exception of the MANOSS method which collected more species than the manual method. In addition, significant differences were observed in the collecting performance for the meiobenthic assemblages, presenting significantly higher densities of meiofauna sampled by the MANOSS compared with the manual collection method, while the airlift device presented an intermediate efficiency. However, taking into account other factors such as cost, ease of use and the scope of each study, none of the methods clearly outperforms the others.